Implementación del protocolo ss7 sobre conexiones entre dos servidores asterisk utilizando los equipos sdh del laboratorío de telecomunicaciones - Azú Campoverde, Alejandro (2010)
The project involved the implementation of the SS7 protocol on E1 connections via two Asterisk servers, using its effect SDH equipment that exist in the Telecommunication Laboratory, performing up to 30 simultaneous calls, which is the ability of an E1. The implementation of this project served to demonstrate the benefits that have to implement the SS7 protocol, and also how to manage efficiently and to ensure both economic and technological resources that offers an E1, for business use. Thus, there were three essential parts to the project: SDH equipment, hardware and software. As for the SDH equipment, we worked with OPTIX HUAWEI 1500B, these are interconnected by optical fiber and each provides us with an E1. The hardware used in each server is the Digium TE205P card, which allows the connection to the E1 and simultaneously interact with Asterisk. As part of the software, SS7 protocol is used for the correct settings between SDH equipment, hardware and software, ensuring the environment of free software.